Metode Dakwah Komunitas Xkwavers dalam Menyampaikan Nilai-Nilai Islam Kepada Trainee Xschool - Vieryall Riva Rovilla (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The Hallyu phenomenon, or Korean Wave, has become a global trend influencing various aspects of life, particularly among Indonesian youth. The popularity of Korean culture, such as K-Pop, K-Drama, fashion, and lifestyle, is not merely a form of entertainment but also impacts the values, lifestyles, and perspectives of teenagers. While this trend brings positive values such as hard work, collaboration, and innovation, there are concerns about its effects on preserving local values and religious teachings. In this context, Islamic da'wah faces both challenges and opportunities to adapt to popular cultural trends. Through a creative approach that utilizes elements of Korean culture, da'wah can be delivered in a way that is relevant and appealing to the younger generation. This study aims to explore the effectiveness of Hallyu-based da'wah strategies and analyze Muslim youth's perceptions of this approach. The results are expected to provide innovative guidance for preserving Islamic values amidst the wave of cultural globalization.